2022
DOI: 10.1177/02676591221137760
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and outcomes with subclavian vein access for crescent jugular dual lumen catheter for venovenous extracorporeal membrane oxygenation in COVID-19 related acute respiratory distress syndrome

Abstract: Introduction Femoral-femoral Veno-Venous ExtraCorporeal Life Support (V-V ECLS) has been associated with higher infections rates, vascular site bleeding complications, and restricted patient mobility. Jugular or bicaval dual lumen V-V ECLS conceptually overcomes some of these adverse factors, but experience has shown that jugular vein cannulation still limits mobility and has increased bleeding complications. Technique and outcomes of subclavian vein single-cannulation with Crescent jugular dual-lumen V-V ECLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Memon et al reported a case series of DLC cannulation via the right SV; the procedure was technically feasible and had a favorable safety profile with a low rate of vascular complications and infection. They also described DLC insertion via the right SV as a practical method for patients requiring long-term V-V ECMO support because it allows greater patient mobility than either jugular or femoral access [ 9 ]. However, complications including pneumothorax, hemothorax, and brachial plexus injury are more commonly reported with SV cannulation compared to IVJ [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Memon et al reported a case series of DLC cannulation via the right SV; the procedure was technically feasible and had a favorable safety profile with a low rate of vascular complications and infection. They also described DLC insertion via the right SV as a practical method for patients requiring long-term V-V ECMO support because it allows greater patient mobility than either jugular or femoral access [ 9 ]. However, complications including pneumothorax, hemothorax, and brachial plexus injury are more commonly reported with SV cannulation compared to IVJ [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subclavian-right atrial ((dl)Vsc-Vra): Several centres have reported success using a subclavian approach 31,32 although this is less established. This may be useful in individuals of shorter stature in which there is inadequate space in the neck to site a jugular cannula.…”
Section: Drainage Of De-oxygenated Blood From the Venous Systemmentioning
confidence: 99%
“…26 Use of a dual lumen cannula means that this advantage is offset by greater flow limitation as the maximum size of commercially available devices is 31-32Fr [27][28][29] with larger sizes possibly associated with a greater rate of complications, including venous thrombosis. 30 Subclavian-right atrial ((dl)Vsc-Vra): Several centres have reported success using a subclavian approach 31,32 although this is less established. This may be useful in individuals of shorter stature in which there is inadequate space in the neck to site a jugular cannula.…”
Section: Introductionmentioning
confidence: 99%